Anisotropic ionic transport properties in solid PEO based electrolytes. (1st December 2022) - Jeanne-Brou, Roselyne; Deseure, Jonathan; Phan, Trang N.T.; Bouchet, Renaud; Devaux, Didier
Highlights: In-plane and through-plane measurements are compared for PEO based electrolytes. Ionic conductivity, transference number and diffusion coefficient are reported. PEO based electrolytes present anisotropic ionic transport properties. In-plane anionic transport is strongly hindered by the presence of structural blocks. An analytical model is proposed to model the in-plane cell voltage relaxation. Abstract: Solid polymer electrolytes (SPE) based on dry poly(ethylene oxide) (PEO) are interesting candidates to develop solid-state lithium (Li) batteries thanks to their stability toward Li metal anode, mechanical properties and flexibility, as well as ionic conductivity high enough for a battery application at temperatures higher than the PEO melting temperatures. To optimize the ionic conductivity, one strategy is to favor in-plane conductivity thanks to its typical higher value in PEO homopolymer electrolyte compared to the through-plane one. Thus, there is the need to understand the in-plane ionic transport properties (ionic conductivity, transference number, and diffusion coefficient) of SPEs depending on their nature and architecture. Indeed, ionic transport in PEO based SPE is due to a complex interplay between different local mechanisms involving the interaction between the PEO chain segments and both cations and anions. The separation of the cationic and anionic mechanisms is thus necessary to distinguish their contributions on the ionic transport anisotropies. Here, we report on the determination by electrochemical methodologies of the cationic and anionic in-plane ionic conductivities, transference numbers and restricted diffusion coefficients for a series of SPEs made of PEO homopolymers (linear), composite (PEO with the addition of nanocellulose), binary (PS-PEO-PS) and single-ion (PSTFSI-PEO-PSTFSI) conducting triblock copolymer electrolytes. The methodology to get each parameter is presented and discussed while COMSOL simulations permit to take into account the geometries of the in-plane cell (positions of the electrodes and SPE dimension). In addition, an analytical model is presented to fit the experimental data of the in-plane cell relaxation (diffusion regime) with a simple equation to determine the in-plane ambipolar diffusion coefficient. We observed that the in-plane anionic transport in SPEs is strongly hindered by the presence of structural blocks leading to an overall in-plane conductivity lower than the through-plane one.